2017
DOI: 10.1080/13548506.2017.1286359
|View full text |Cite
|
Sign up to set email alerts
|

Perceived sources and levels of stress, general self-efficacy and coping strategies in clinical dental students

Abstract: The aims of this study were to identify sources of stress among clinical students and to evaluate the students' perceived levels of stress, general self-efficacy and effective coping strategies in a private dental school environment. The study group consisted of 130 undergraduate clinical dental students in a Turkish private dental school, during the academic year 2014-2015. The students were surveyed using modified version of the dental environment stress (DES) survey, the perceived stress scale, the general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 10 publications
6
24
2
2
Order By: Relevance
“…Self‐reported experience of anxiety and mental exhaustion before starting dental education was associated with being anxious after working with patients. This finding is in contrast to a study amongst pre‐clinical dental students that found no association between history of psychiatric treatment and stress, but it is in line with a study amongst clinical students that showed higher self‐efficacy amongst those who had no history of psychiatric treatment . It must be noted that the latter study requested information on more severe mental health conditions than those in our study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Self‐reported experience of anxiety and mental exhaustion before starting dental education was associated with being anxious after working with patients. This finding is in contrast to a study amongst pre‐clinical dental students that found no association between history of psychiatric treatment and stress, but it is in line with a study amongst clinical students that showed higher self‐efficacy amongst those who had no history of psychiatric treatment . It must be noted that the latter study requested information on more severe mental health conditions than those in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Some work has been done to improve dental students' learning environment, like teaching stress management in the UK and mindfulness in Germany . Studies from India and Turkey suggested that spiritual health/religion may increase students' coping strategies . However, although clinical work is one of the greatest stressors in dental education, it has not received much attention in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The experiences most frequently cited as being stressful for students related to thoughts about the magnitude and multiplicity of the tasks that were required to be performed and the feelings of anxiety and pressure associated with these thoughts. This is consistent with the majority of such studies conducted with student samples, and, therefore, reiterates the fact that students experience enormous levels of stress during this developmental stage of life in which they are especially vulnerable to the deleterious effects of stressful experiences. The coping strategies employed by students in our sample, and the overwhelming preference for emotion‐based rather than problem‐based coping strategies, are likely the result of the social and cultural context.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, there is substantial evidence that university students, and in particular those of medical and health‐related disciplines, experience an inordinate degree of study and work‐related stress. A multitude of studies from a variety of cultures and regions reported elevated levels of perceived stress among students from medical, dental, nursing, and mental health professions …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Numerous studies examining stress in dental students report that the dental learning environment is stressful, 2,[4][5][6][7][8] and identified academics, finances, and clinical workloads as the main sources of stress. 4,[7][8][9][10] Several studies report that perceived sources of stress vary by year in dental school. [10][11][12] For example, one study found that fourth year and graduating students were less concerned about class workload, clinical training, and failing courses, but more concerned about their professional future, whereas entry-level students were more concerned about time for relaxation.…”
Section: Introductionmentioning
confidence: 99%